Globalization on trial the human condition and the information civilization (Ottawa International Development Research Centre ; West Hartford, Conn. Kumarian Press, 2000)
"What is the human condition at the dawning of the global age? Drawing upon his own extensive experience, as well as upon the thoughts of Western and "non-Western" scholars and philosophers, Farhang Rajaee provides a fresh and critical inquiry into th e nature of globalization." "Globalization on Trial challenges the conventional view that equates globalization with the expansion of the capitalist economic system. With a broad historical and holistic brush, the author presents a view of globalization that is both multidisciplinary and multicultural. What opportunities must we seize? What dangers must we overcome? Rajaee examines human governance and the paradox of globalism and nationalism (or "nativism"), providing a particularly fresh perspective on Islamic civilization. He also focuses on our education system and how it will have to adapt to meet the new challenges of our global, information age." "Globalization on Trial will interest researchers, scholars, and students in the social sciences and, particularly, the humanities; donors, development organizations, NGOs, and development practitioners; and anyone concerned with how globalization and the information revolution are affecting the nature of human civilization, and with the interaction between Islamic and Judeo-Christian (or "Western") civilization. Book jacket."--Jacket.
Foreword / John Sigler -- Ch. 1. The New Creation. A new world in the making. Approach and method -- Ch. 2. A Theory of Globalization. Political approach, the end of civility. Economic approach, the end of geography. Cultural approach, the end of obje ctivity. Religious and secular radical approach, the end of inquiry. Critique of these paradigms. Civilizational approach, the restoration of politics -- Ch. 3. The Coming of the Information Civilization. Technological society. The information revolution. Features of the new civilizations. Political pluralism, multilateralism. Economic pluralism, production sharing. Cultural pluralism, multiculturalism. The global public sphere, the Internet. Clash or dialogue of civilizations -- Ch. 4. The Future of Global Governance. Challenges. Responses.
Includes bibliographical references (p. 133-144) and index.
Keywords: Globalization; Information technology -- Social aspects; International relations; Electronic books; Mondialisation (âEconomie politique); Relations internationales; Technologie de l'information -- Aspect social; SOCIAL SCIENCE -- Anthropology -- General; SOCIAL SCIENCE -- Regional Studies; Cultuurverandering; Informatiemaatschappij; Internationalisatie; Electronic books